2017
DOI: 10.24908/pocus.v2i2.13279
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Project: Does formal bedside training of medical students with a FAST exam increase their knowledge and comfort level with ultrasound use in a community family medicine practice setting?

Abstract: As point of care ultrasound (PoCUS) becomes increasingly popular and a standard of care in many clinical settings, the interest for integration in medical undergraduate curriculum is also growing [1]. This project aims to assess whether formal bedside Focused Abdominal Scan for Trauma (FAST) exam training of medical students increases their knowledge and comfort with the use of bedside ultrasound in a family medicine setting at Queen’s University. Third year medical students (n=18) were recruited to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With growing student interest in cardiac ultrasound examination [8], multiple studies have demonstrated feasibility and benefits of integrating cardiac POCUS into the undergraduate medical education (UME) curriculum [9][10][11][12][13][14]. A comprehensive review article on cardiac POCUS in medical school education described that 12 medical schools in the United States, Canada, Norway, United Kingdom, Israel, Poland, and China have incorporated cardiac POCUS curricula [15].…”
Section: Introductionmentioning
confidence: 99%
“…With growing student interest in cardiac ultrasound examination [8], multiple studies have demonstrated feasibility and benefits of integrating cardiac POCUS into the undergraduate medical education (UME) curriculum [9][10][11][12][13][14]. A comprehensive review article on cardiac POCUS in medical school education described that 12 medical schools in the United States, Canada, Norway, United Kingdom, Israel, Poland, and China have incorporated cardiac POCUS curricula [15].…”
Section: Introductionmentioning
confidence: 99%
“…With growing student interest in cardiac ultrasound examination [8], multiple studies have demonstrated feasibility and bene ts of integrating cardiac POCUS into the undergraduate medical education (UME) curriculum [9][10][11][12][13][14]. A comprehensive review article on cardiac POCUS in medical school education described that 12 medical schools in the United States, Canada, Norway, United Kingdom, Israel, Poland, and China have incorporated cardiac POCUS curricula [15].…”
Section: Introductionmentioning
confidence: 99%